Oncolytic herpesvirus therapy for mesothelioma – A phase I/IIa trial of intrapleural administration of HSV1716. (December 2020) - Danson, Sarah J.; Conner, Joe; Edwards, John G.; Blyth, Kevin G.; Fisher, Patricia M.; Muthana, Munitta; Salawu, Abdulazeez; Taylor, Fiona; Hodgkinson, Elizabeth; Joyce, Patrick; Roman, Jennifer; Simpson, Kathleen; et al.
Highlights: Mesothelioma is often multifocal within the pleural cavity. The oncolytic virus, HSV1716 was given safely intrapleurally. Intrapleural HSV1716 produces an immune response. Abstract: Objectives: Malignant Pleural Mesothelioma (MPM) remains a major oncological challenge with limited therapeutic options. HSV1716 is a replication restricted oncolytic herpes simplex virus with anti-tumor effects in multiple cell lines including MPM. Intrapleural treatment appeals because MPM is typically multifocal but confined to the pleura, and distant metastases are uncommon. We assessed the safety and possible efficacy of intrapleural HSV1716 for inoperable MPM. Materials and methods: Patients with MPM received 1 × 10 7 iu HSV1716 injected via an indwelling intrapleural catheter (IPC) on one, two or four occasions a week apart. The primary endpoint was the safety and tolerability of HSV1716. Secondary endpoints were assessment of HSV1716 replication, detection of immune response and evaluation of tumor response. Results: Of thirteen patients enrolled, five had received previous pemetrexed-cisplatin chemotherapy, and eight were chemotherapy naïve. Three patients were enrolled to receive one dose, three patients to two doses and seven patients to four doses. The treatment was well-tolerated with few virus-related adverse events and no dose limiting toxicities. Twelve patients were evaluable for response, as one patient withdrew early after a catheter fracture. There was evidence of viral replication/persistence in pleural fluid in seven of the twelve patients. Induction of Th1 cytokine responses to HSV1716 treatment occurred in eight patients and four patients developed novel anti-tumor IgG. No objective responses were observed but disease stabilization was reported in 50 % of patients at 8 weeks. Conclusions: Intrapleural HSV1716 was well-tolerated and demonstrated an anti-tumor immune response in MPM patients. These results provide a rationale for further studies with this agent in MPM and in combination with other therapies.